Enhancement of microstructure characteristic and dielectric constant of BaMn0.05Ti0.95O3 ceramics. Issue 1 (1st December 2022) - Suherman, B; Nurosyid, F; Handoko, E; Khairuddin; Sandi, D K; Hasanah, L U; Agustina, F R; Puspita, N F S; Iriani, Y
Abstract: Barium Titanate or BaTiO3, a ferroelectric material with good dielectric properties, is widely studied. The performance of BT is influenced by synthesis and doping. Here, Barium Titanate has been doped with Manganese via the co-precipitation procedure sintered at 900°C and 1000°C. The purposes of this study were to examine the microstructure and dielectric constant of BaMn0.05Ti0.95O3 with variation sintering temperatures at 900°C and 1000°C. The testing employed X-Ray Diffraction (XRD), Fourier Transform Infrared (FTIR), and Resistance Capacitance Inductance (LCR Meter). The XRD data exposed that the crystal size of the BaMn0.05Ti0.9503 sample enlarged from 48.27 nm to 72.41 nm with increasing sintering temperature. The analysis results using FTIR exhibited the existence of Ba-O and Ti-O bonds which confirmed the perovskite structure of BaTiO3. FTIR data also indicated the presence of C-H atomic bonds, which is the peak of impurities in the carbonate phase. The C-H bond vibration decreased at the higher sintering temperature. The dielectric constant value was obtained from the measurements using an LCR meter. In conclusion, increasing the sintering temperature improved the dielectric constant of BaMn0.05Ti0.95O3 from 119 to 386.